Sickness absence from back pain, psychosocial work characteristics and employment grade among office workers - Hemingway, H.; Shipley, Martin J.; Stansfeld, Stephen; Marmot, Michael (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'The relation between psychosocial work characteristics, employment grade, and sickness absence due to back pain was studied among office workers.' ' METHODS ': 'Base-line questionnaire data and sickness absence data collected continuously with a mean of 4 years of follow-up were analyzed. The subjects were 6894 men and 3414 women aged 35 to 55 years at recruitment. The main outcome measures were short (³7 days) and long (>7 days) absences due to back pain.' ' RESULTS ': 'There was a strong inverse association between employment grade and rate of absences due to back pain (P for linear trend
Keywords: cohort study; etiology; MSD; musculoskeletal disorder; prospective study; socioeconomic status